Therapeutic and Adverse Effects of Metformin in Diabetes: A Review Article: Life Sciences-Endocrinology - Mohammed Alatawi, Abdulaziz; Fayez Albogami, Afaf; Salem Aldharman, Sarah; Mohammed Majrashi, Salwa; Saleh Alghamdi, Ruba; Essa Boobaid, Nawari; Mirghani Mohamed, Hyder Osman (International Journal of Life Science and Pharma Research, 2022)
Metformin is the most often prescribed first-line oral antidiabetic. This review summarized the effects of Metformin on the body, its role in diabetes prevention and treatment, and the adverse effects of metformin administration. A PubMed search for metformin-related papers in diabetic patients was performed. We included articles on any metformin oral dosage in people with or without type 2 diabetes that reported favorable and unfavorable outcomes. Relevant studies from the references provided were reviewed. Metformin controls the blood glucose level by multiple mechanisms. These include increasing the cell sensitivity to insulin and reducing endogenous glucose secretion by the liver. Also, Metformin has been shown to assist in weight reduction in obese patients. Some early investigations showed that lifestyle changes and Metformin significantly reduced the incidence of diabetes in high-risk people, and lifestyle interventions were more effective than Metformin. Some trials indicated Metformin was not associated with any significant endangerment or advantage in terms of cardiovascular incidents. However, Metformin tended to be more effective in longer trials involving younger individuals regarding cardiovascular outcomes. The microvascular complication prevalence was insignificant between Metformin and other treatment interventions including placebo and lifestyle interventions. The gastrointestinal symptoms are common with metformin use as compared to placebo. Metformin increased the risk of lactic acidosis, especially in moderate and severe renal impairment settings, thus considered contraindicated. However, due to the low reported incidence of lactic acidosis associated with Metformin and the potential protective properties on the kidney, heart, and liver, it is advised to carefully balance the risk and benefits of Metformin when treating diabetes. In addition, Metformin has been shown to cause consequences other than gastrointestinal symptoms, such as vitamin B12 deficiency which can lead to hematologic issues, such as anaemia and peripheral neuropathy. Thus, periodic measurement of vitamin B12 for individuals treated with Metformin is recommended.